The solvent effect, preferential solvation of metformin hydrochloride in binary mixed solvents of methanol/ethanol + water mixtures from 278.15 K to 323.15 K - Adel Noubigh; Abdalazeem A. Omar; Manef Abderrabba (South African Journal of Chemical Engineering)
This study provides a novel quantitative analysis of metformin hydrochloride (MET-HCl) solvation behavior in binary solvents mixtures of methyl alcohol and water, as well as ethyl alcohol and water, addressing critical gaps in understanding its solubility mechanisms for pharmaceutical formulation. We employed the inverse Kirkwood-Buff integrals (IKBI) method to extract key parameters from the solution thermodynamic properties of MET.HCl, yielding valuable insights into its behavior. The findings reveal that MET.HCl is sensitive to solvation effects, with the values of δx1,MET-HCl exhibiting a non-linear relationship with the proportion of solvent (1) in the two solvent mixtures. Specifically, in both the methyl alcohol/water and ethyl alcohol/water systems, all alcoholic aqueous mixture compositions exhibit negative δx1,MET-HCl values. Overall, our results reveal that MET-HCl exhibits preferential solvation by water, with a significantly greater magnitude of preferential solvation observed in ethyl alcohol /water mixtures compared to methyl alcohol /water mixtures. This enhanced solvation by water may be attributed to the disordered structure of the alcohol molecules surrounding the polar regions of MET-HCl. The influence of solvent composition on the molar fraction solubility of MET-HCl was investigated using the Kamlet-Taft linear solvation energy relationship model. The KAT-LSER model revealed that solvent polarity (π*) and ability to accept hydrogen bonds (α) were key factors in MET-HCl dissolution in methyl alcohol and water, as well as ethyl alcohol and water.